Maximizing Problem-Solving Abilities through Hybrid Problem-Based Learning with Formative Assessment - Jufriadi, Akhmad; Ayu, Hena Dian; Kumalasari, Tutut; Kusumawati, Astrini Dewi; Alatas, Fathiah; Budiyono, Agus (UIN Sunan Gunung Djati Bandung, 2024)
Problem-solving is one of the abilities students must master when learning physics. Teachers must try to find solutions to improve their students' problem-solving abilities. This research aims to explore students' problem-solving abilities regarding work and energy concepts and determine improvements and differences in students' problem-solving abilities regarding work and energy material by applying the Hybrid Problem-Based Learning model with formative assessments. This research method uses a mixed-method approach with an embedded experimental design. The research sample consisted of 35 high school students. Qualitative and quantitative data were analyzed simultaneously. Qualitative data was analyzed using open coding and generalization, while quantitative data was analyzed using the n-gain score test. The results of the quantitative analysis show that students' problem-solving abilities increased from an average of 38.74 to 80.65. Calculating the n-gain value obtained a score of 0.68, which indicates that hybrid problem-based learning with formative assessment effectively improves students' problem-solving abilities regarding the concepts of work and energy. The results of the qualitative analysis revealed students' difficulties in solving problems. Some of the challenges found include 1) students needing help translating test items into graphic representation, 2) students needing help determining the specific application of physics, and 3) some students still needing help carrying out mathematical procedures. Teachers can use the findings of this research as a basis for designing and planning learning in the classroom to improve student's problem-solving abilities